Qualitative Review of Stories Told: Anecdotes of CFO – CEO Relationships - Brown Sr., Theodore (Archives of Business Research, 2019)
The basis of this qualitative examination was incited by the notion that the perceptions of Seventh-day Adventist (SDA) Local Conference leadership substantially effects how the relationships of Chief Financial Officers (CFOs/Treasurers) and Chief Executive Officers (CEOs/Presidents) are viewed and function as members of their conference leadership team . In the past, Chief Financial Officers (CFOs) and Chief Executive Officers (CEOs) have historically functioned in their own professional executive compartments within their organizations rather than partnering together as cooperative teammates. The 21st Century’s, however, has forever changed how CFOs and CEOs relate to each other in the workplace due to the inception of governmental regulations called the Sarbanes-Oxley Act which was passed to address major corruption in large USA businesses and organizations, major non-compliance in accounting practices, extensive financial reporting fraud, institutional mis-management, board governance, CFO and CEO accountability. The impact of Sarbanes-Oxley has also influenced the relational practices of CFOs and CEOs in Seventh-day Adventist (SDA) conferences. A Mixed-Methods sequential exploratory research design was used with primary data for this study purposefully selected, collected and analyzed (coding, patterns, trends and themes) from qualitative focus group interviews with four local conference CFOs and CEOs, N=8, located in the United Stated of America (USA). Discussion and Conclusion are explored and disclosed, and the Implications of CFO and CEO relationship on organizational effectiveness, efficiency, and climate are presented.